Tailoring patches on particles: a modified microcontact printing routine using polymer-functionalised stamps. Issue 68 (6th August 2019) - Sperling, Marcel; Reifarth, Martin; Grobe, Richard; Böker, Alexander
Abstract : We present a microcontact printing (μCP) routine suitable to transfer low molecular weight compounds as ink (LMWI) on silica microparticles. Abstract : Herein, we report a modified microcontact printing (μCP) routine suitable to introduce particle patches of a low molecular weight ink (LMWI) on porous SiO2 microparticles. Thereby, patch precision could be significantly improved by utilising stamps which have been surface-functionalised with grafted polymers. This improvement was evaluated by a profound software-assisted statistical analysis.